2022
DOI: 10.1155/2022/7489023
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Application of Sandwich Teaching Method Based on Network Platform in Rehabilitation Nursing Teaching in Postepidemic Era

Abstract: Rehabilitation nursing teaching is one of the key points of nursing teaching. The quality of rehabilitation nursing teaching directly affects the comprehensive ability of clinical interns. Therefore, teachers must further deepen the reform of clinical nursing teaching, improve the teaching system, and explore effective clinical nursing teaching methods. This paper introduces the application of the network teaching mode based on sandwich in rehabilitation nursing teaching, which provides guidance and help for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Clinical practice ability is a key indicator for testing the quality of nursing education and the effectiveness of clinical teaching ( 2 , 3 ). There are many uncertainties in clinical nursing, which require students to possess professional ability and operational skills ( 4 ). Therefore, nursing training should focus on cultivating students’ clinical skills and emergency response abilities ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical practice ability is a key indicator for testing the quality of nursing education and the effectiveness of clinical teaching ( 2 , 3 ). There are many uncertainties in clinical nursing, which require students to possess professional ability and operational skills ( 4 ). Therefore, nursing training should focus on cultivating students’ clinical skills and emergency response abilities ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%